Short Survival Time after Palliative whole Brain Radiotherapy: Can We Predict Potential Overtreatment by Use of a Nomogram? - Nieder, Carsten (J Cancer, 2017)
Background: Many patients with brain metastases undergoing whole brain radiotherapy (WBRT) have very limited survival. The purpose of this study was to validate a nomogram derived from a large American database and to examine its ability to better predict short survival (cut-off 2 months) than previous models. Material and Methods: This retrospective study included 254 European patients treated with primary WBRT. In addition, an exploratory analysis of patients managed with best supportive care (BSC) was performed too. Results: Median survival after WBRT was 3.0 months. The median nomogram point sum was 122 (range 31-212). The nomogram-predicted median survival for a patient with 122 points is 3.3 months. Despite the nomogram's ability to stratify the patients into different prognostic groups, the survival curves of patients with intermediate point sum in the range of 90-139 points were largely superimposable. The poorest prognostic group with ≥180 points had a median and maximum survival of 1.8 and 4.6 months, respectively. Among these 18 patients (7%) 9 survived for less than and 9 for more than 2 months. Comparable survival outcomes were observed after BSC in a smaller group of 8 patients with ≥180 points. Conclusions: Because of several differences between the original and validation findings, the nomogram should be examined in additional large databases. Its ability to predict poor survival is promising and possibly comparable to our previously published models. The final goal of developing a validated model that allows poor prognosis patients to safely forego WBRT without compromising survival or quality of life requires further research efforts.